Effect of Fe3O4 Nanoparticles Modified by Citric and Oleic Acids on the Physicochemical and Magnetic Properties of Hybrid Electrospun P(VDF-TrFE) Scaffolds; Polymers; Vol. 15, iss. 14 - Botvin V. V. Vladimir Viktorovich; Fetisova A. A. Anastasiya Alekseevna; Mukhortova Yu. R. Yulia Ruslanovna; Vagner D. Dmitry; Kazantsev S. O. Sergey Olegovich; Surmeneva M. A. Maria Alexandrovna; Kholkin A. L. Andrei Leonidovich; Surmenev R. A. Roman Anatolievich (2023, 2023)
Title screen